Development of an improved protocol for heterogeneous waste characterisation / Sivapalan Kathiravale - Sivapalan , Kathiravale (2019)
Waste Management in Malaysia over the last 15 to 20 years has been on the brink of change. Currently, waste management method is still very dependent on landfilling but there have been technologies introduced like incinerators and Material Recovery Facilities. Almost all of these facilities have either been closed or operating at far below the designed parameters due to the in-ability of the treatment process to handle the complexity of the waste being delivered for treatment. Investigations lead to the fact that the waste characteristics did not reflect the actual condition of the waste. The problem with waste management in Malaysia is the fact that no source separation is in practice. This is compounded with the fact that Malaysia is a multi-cultured society and a heaven for food. These facts only add to the variety of waste that is generated, making it impossible to predict the kind and quantity of waste that is generated. Addressing these problems, waste characteristics from 2000 to 2014 was used in this study as a basis towards inferring relationships between these data. The objective was to identify which were the best protocol for characterization of waste, taking into account the various methods that were available while looking at some critical parameters in the characteristics; i.e. moisture content and the calorific value of the waste. Methods on how to sample the waste and what was the best approach to sample a 5 ton truck load of waste, to give the most accurate but yet not costly and time consuming were studied. Another analysis which contributed strongly was the number of components into which the wastes are sorted into. In the year 2000 the number of components that the waste was sorted into was less than 15 components but by 2012 the number of components had increased to about 25 components, thus the re-distribution of the weight percentage of the waste component. Next, was to look into the method by which moisture content was recorded and analysed during a sampling process. There was a big variance between the amounts of moisture reported versus the actual amount of water observed in the waste samples. Finally, the analysis of calorific value requires very tedious analysis which was time consuming and expensive. This study used equations to predict the calorific value of the waste. The results showed that the Cone and Quarter method was sufficiently representative of the truck load of the waste while being able to have the necessary accuracy to portray the waste characteristics while being affordable and timely. The study proved that waste must be sorted into as many components as possible to understand the waste better. As for the moisture content analysis, the study proved that there was a need to address the leachate and the moisture content during the sampling phase which could contribute up to 20% more moisture in the sample. A predictive method using equations that was formed based on local waste characteristics such as the physical composition of the waste, the proximate content and the ultimate content of the waste was used in this study. These equations were then tested with available equations to predict the calorific value of the waste. This study was able to prove that the physical parameters equation gives the best prediction. Based on the above findings, the study was able to show an improved protocol that could be adopted for the batter understanding and solving the waste generated in Malaysia.